The importance of the pharmacist in the treatment of type 2 Diabetes mellitus (Research, Society and Development, 2021)
In the search to confirm the importance of the pharmacist in the treatment of DM, the aim of this article is to identify, through the relevant literature, the Pharmaceutical Care provided to patients with type 2 Diabetes Mellitus. This is an Integrative Literature Review of type 2. qualitative, using the databases: Scielo, Pubmed and Lilacs. Type 2 Diabetes Mellitus is a metabolic disease that has been growing a lot in recent times due to the sedentary lifestyle that people adhere to, in addition to an inadequate diet, this population group needs to use oral hypoglycemic agents or insulin to maintain blood glucose levels within normal limits. The pharmacist is the professional trained to advise on drug treatment and even non-drug treatment, all precautions with drug interaction, insulin administration or storage must be explained to the patient so that he can perform the treatment effectively. Thus, it is concluded that Pharmaceutical Care is essential to guide and raise awareness of DM patients, working together with the multidisciplinary team.